Preparation method of pre-lithiated battery cell

The nanofiber membrane was prepared by electrospinning and prelithiated, which solved the problem of lithium ion loss during the first charge and discharge of lithium ion batteries, and improved the electrical performance and safety of the battery.

CN119890464APending Publication Date: 2025-04-25HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510020534.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Lithium-ion batteries consume lithium ions during the first charge and discharge to form SEI film, resulting in low efficiency and irreversible loss of capacity for the first time. The existing physical contact pre-lithium methods pose safety risks.

Method used

Flat-plate nanofiber membranes were prepared by electrospinning and prelithiated by liquid or solid phase treatment. The nanofiber membrane adsorbed lithium ions or lithium powder to react with the negative electrode surface after the battery was injected into liquid.

Benefits of technology

It improves the electrical performance of the battery, enhances lithium storage capacity and lithium ion transmission, reduces safety risks, and avoids adverse reactions from physical contact with prelithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231228010000081
    Figure BDA0005231228010000081
Patent Text Reader

Abstract

The invention discloses a pre-lithiation cell preparation method, which comprises: A, drying polymer powder, placing the dried polymer powder and an additive in an organic solvent, stirring and dissolving to form a spinning solution, and preparing a flat plate nanofiber membrane through an electrostatic spinning method, carrying out liquid-phase treatment or solid-phase treatment on the flat nanofiber membrane to finish pre-lithiation; step B, performing hot pressing on a PP base membrane and the pre-lithiated flat plate nanofiber membrane through a roller of a calender to form a composite membrane; the composite diaphragm has relatively good liquid absorption capability, is beneficial to lithium ion transmission in the charging and discharging process of the battery and is high in safety, and on the other hand, after the nanofiber membrane is treated and liquid is injected into the battery, a lithium complex reacts with the surface of a negative electrode to form an SEI membrane, so that the loss of active lithium in the first charging and discharging process is made up, and the service life of the battery is prolonged. Therefore, the electrical performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a method for preparing a pre-lithiation battery cell. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density, good cycle life and safety performance, and are widely used in industrial fields such as mobile phones, automobiles, and aerospace. However, when lithium-ion batteries are charged and discharged for the first time, they will consume lithium ions from the positive electrode to form a SEI film, resulting in low initial coulombic efficiency and irreversible capacity loss. Therefore, in order to ensure the initial coulombic efficiency, capacity and cycle stability of the battery, it is necessary to replenish lithium externally to make up for the lithium source consumed by the formation of the SEI film during the first charge.

[0003] In the existing practice of replenishing lithium at the negative electrode through physical contact pre-lithiation, the physical contact pre-lithiation is to directly contact lithium powder or lithium sheets with the negative electrode. This method realizes spontaneous lithium insertion of active materials in the form of internal short circuit, making the lithium insertion more uniform. However, both lithium sheets and lithium powder have extremely high reactivity and environmental sensitivity, which can easily lead to safety risks. For this reason, we propose a method for preparing pre-lithiation battery cells. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a pre-lithiation battery cell to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a pre-lithiation battery cell, comprising the following steps:

[0006] Step A: After the polymer powder is dried, it is placed in an organic solvent together with an additive, stirred and dissolved to form a spinning solution, a flat nanofiber membrane is prepared by an electrospinning method, and then the flat nanofiber membrane is subjected to liquid phase treatment or solid phase treatment to complete pre-lithiation;

[0007] Step B: hot pressing the PP base film and the pre-lithiated flat nanofiber membrane through a calender roller to form a composite separator;

[0008] Step C: stacking the composite diaphragm, negative electrode, composite diaphragm, positive electrode, composite diaphragm, and negative electrode into a unit body, wherein the base film surface of the composite diaphragm is attached to the positive electrode, and the nanofiber membrane surface is attached to the negative electrode, and then hot pressing a plurality of the unit bodies to complete the battery cell assembly.

[0009] It is convenient to remove moisture from the polymer powder to ensure its stability and uniformity in the subsequent dissolution process, stretch the polymer solution into nanoscale fibers by applying high voltage, and collect them on a conductive receiving plate to form a uniform nanofiber membrane, which is pre-lithiated through liquid or solid phase to adsorb lithium ions or lithium powder so that it can react with the negative electrode surface after the battery is filled with liquid to form a SEI membrane.

[0010] Preferably, the polymer powder in step A is one or more of polyacrylonitrile, polymethyl methacrylate, acrylic acid-maleic anhydride copolymer, polytetrafluoroethylene, and polyvinylidene fluoride.

[0011] These materials generally have good chemical stability and high temperature resistance.

[0012] Preferably, the weight average molecular weight of the polymer powder in step A is 30,000-250,000, and the drying time during the drying is 12-24 hours.

[0013] The weight average molecular weight covers a variety of polymers from low molecular weight to high molecular weight, and usually has the advantages of better mechanical properties, thermal properties, and solubility.

[0014] Preferably, the organic solvent in step A is one or more of N,N-dimethylformamide, dimethyl sulfoxide and acetone.

[0015] Easy to dissolve a variety of compounds.

[0016] Preferably, during the dissolution in step A, the solution is heated and dissolved under the action of a multi-head magnetic stirrer, the dissolution time is 12-24 hours, and the dissolution temperature is 50-80°C.

[0017] It is convenient to improve the dissolution efficiency so as to quickly support the solution.

[0018] Preferably, in the spinning solution of step A, the mass fraction of the polymer powder is 10-30 parts, the mass fraction of the additive is 0-5 parts, and the mass fraction of the organic solvent is 60-90 parts.

[0019] By controlling the mass fractions of polymer powder, additives and organic solvents, the performance of the spinning solution can be optimized, ensuring the smooth spinning process and obtaining fiber products with ideal properties. The proportions in the formula make the spinning solution have good solubility and fluidity, and can also improve the later performance of the fiber by adding appropriate amounts of additives.

[0020] Preferably, the liquid phase treatment step in step A is: immersing the prepared flat nanofiber membrane in a 45°C lithium-biphenyl / tetrahydrofuran solution or a naphthalene-2-methyl-tetrahydrofuran lithium solution for 24-48 hours, with a solution concentration of 0.1M-1M, and then drying in an oven at 45°C for 12-24 hours.

[0021] It is convenient for the nanofiber membrane to absorb the lithium-containing complex in the solution, so as to make up for the loss of active lithium in the initial charge and discharge process, thereby improving the electrical performance of the battery.

[0022] Preferably, the solid phase treatment step in step A is: placing a porous lithium foil or lithium foil between the base membrane and the nanofiber membrane, and then performing hot pressing.

[0023] It is convenient to absorb lithium powder and make up for the loss of active lithium during the initial charge and discharge process.

[0024] Preferably, the nanofiber membrane prepared by electrospinning in step A has a diameter of 150-500 nm, a porosity of 50%-80%, and a thickness of 3 um-6 um.

[0025] It is convenient to better adsorb lithium powder or lithium ions.

[0026] Preferably, in step C, the hot pressing pressure of the battery cell assembly is 5-10t, and the hot pressing temperature is 70-95°C.

[0027] It is convenient to perform pressure treatment on the battery cell in a heated state to ensure sufficient contact and bonding force between the various layers of material in the battery cell, thereby avoiding gaps or uneven compaction inside the battery cell.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention prepares a nanofiber membrane through an electrostatic spinning method. The nanofiber membrane has a high porosity and specific surface area. It is subjected to liquid-phase or solid-phase pre-lithiation. The nanofiber membrane fully absorbs lithium ions or lithium powder, with the aim of making the reaction in the pre-lithiation process more peaceful and improving the lithium storage capacity of the diaphragm. After the pre-lithiation treatment, the lithium powder or lithium ions contained on the nanofiber membrane react on the surface of the negative electrode to complete the pre-lithiation of the battery cell with high safety. Since the composite diaphragm has good liquid absorption capacity, it is beneficial to the lithium ion transmission during the battery charging and discharging process. On the other hand, after the nanofiber membrane is treated, after the battery is filled with liquid, the lithium complex reacts with the negative electrode surface to form an SEI film, which makes up for the loss of active lithium in the first charging and discharging process, thereby improving the electrical performance of the battery. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] The present invention provides a technical solution: a method for preparing a pre-lithiation battery cell, comprising the following steps:

[0033] Step A: drying the polymer powder to a moisture content of 50-500ppm, then placing the dried polymer powder and additives in an organic solvent, stirring and heating with a stirrer to dissolve to form a spinning solution, placing the spinning solution in an injection container, and preparing a flat nanofiber membrane by an electrospinning method, the voltage of the electrospinning device is 5kv-20kv, the spinning solution flow rate is 0.05-0.3mL / min, and then the flat nanofiber membrane is subjected to liquid phase treatment or solid phase treatment to complete pre-lithiation;

[0034] Step B: hot pressing the PP base film and the pre-lithiated flat nanofiber membrane through calender rollers, with the upper roller temperature being 150-200° C., the lower roller temperature being 90-150° C., and the thickness of the support film base film being 6-9 μm, to form a composite separator;

[0035] Step C: stacking a composite diaphragm, anode, composite diaphragm, cathode, composite diaphragm and cathode into a unit body, wherein the base film surface of the composite diaphragm is attached to the cathode, and the nanofiber film surface is attached to the cathode. The cathode active material is graphite, silicon oxide, silicon carbon or other silicon-doped compounds. Then, multiple units are hot pressed to complete the battery cell assembly. The battery cell is composed of 10-30 units.

[0036] It is convenient to remove moisture from the polymer powder to ensure its stability and uniformity in the subsequent dissolution process, and to stretch the polymer solution into nano-scale fibers by applying high voltage and collect them on a conductive receiving plate to form a uniform nanofiber membrane. Pre-lithiation is carried out through the liquid phase or solid phase to adsorb lithium ions or lithium powder so as to react with the negative electrode surface after the battery is filled with liquid to form an SEI film. The present invention performs pre-lithiation by contacting the composite diaphragm that adsorbs lithium ions or lithium powder with the negative electrode sheet, and the reaction is more peaceful, avoiding physical contact pre-lithiation that causes safety risks by directly contacting lithium powder or lithium sheet with the negative electrode.

[0037] Preferably, the polymer powder in step A is one or more of polyacrylonitrile, polymethyl methacrylate, acrylic acid-maleic anhydride copolymer, polytetrafluoroethylene, and polyvinylidene fluoride.

[0038] Polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), acrylic acid-maleic anhydride copolymer (P(MA-MA)), polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), these polymer powders can be used alone or in combination, and generally have good chemical stability and high temperature resistance, so that they are suitable for use in a variety of electrochemical reaction environments.

[0039] Preferably, the weight average molecular weight of the polymer powder in step A is 30,000-250,000, and the drying time during drying is 12-24 hours.

[0040] The weight average molecular weight covers a variety of polymers from low molecular weight to high molecular weight, and usually has the advantages of better mechanical properties, thermal properties, and solubility. Polymers in this molecular weight range usually have better solubility and processing properties, especially when the polymer requires solution processing.

[0041] Preferably, the organic solvent in step A is one or more of N,N-dimethylformamide, dimethyl sulfoxide and acetone.

[0042] They are all commonly used polar solvents that are easy to dissolve a variety of compounds.

[0043] Preferably, during the dissolution in step A, the solution is heated and dissolved under the action of a multi-head magnetic stirrer, the dissolution time is 12-24 hours, and the dissolution temperature is 50-80°C.

[0044] It is convenient to improve the dissolution efficiency so as to quickly support the solution.

[0045] Preferably, in the spinning solution of step A, the mass fraction of the polymer powder is 10-30 parts, the mass fraction of the additive is 0-5 parts, and the mass fraction of the organic solvent is 60-90 parts.

[0046] The ratio of polymer powder and solvent determines the viscosity and fluidity of the spinning solution. A higher solvent ratio of 60-90 parts ensures that the polymer can be fully dissolved and the spinning solution has appropriate fluidity, which is conducive to the smooth progress of the spinning process. A moderate polymer powder ratio of 10-30 parts helps to obtain a stable fiber structure during the spinning process. If the polymer concentration is too low, the spun fiber may be too thin and have poor strength; if the polymer concentration is too high, the spinning solution may be too viscous, resulting in difficulty in spinning. Although the additives account for a small proportion of 0-5 parts by mass, they can improve the stability of the spinning solution, adjust the properties of the fiber, or provide specific functional properties in the subsequent heat treatment process. For example, antioxidants, antistatic agents, plasticizers, etc. can improve the durability and elasticity of the fiber. By controlling the mass fractions of polymer powder, additives and organic solvents, the properties of the spinning solution can be optimized, ensuring the smooth progress of the spinning process and obtaining fiber products with ideal properties. The ratio in the formula makes the spinning solution have good solubility and fluidity, and can improve the later performance of the fiber by adding an appropriate amount of additives.

[0047] Preferably, the liquid phase treatment step in step A is: immersing the prepared flat nanofiber membrane in a 45°C lithium-biphenyl / tetrahydrofuran solution or a naphthalene-2-methyl-tetrahydrofuran lithium solution for 24-48 hours, with a solution concentration of 0.1M-1M, and then drying in an oven at 45°C for 12-24 hours.

[0048] These two solutions contain lithium ions. Lithium ions are usually highly active in chemical reactions and can promote specific chemical reactions or cause changes in the surface structure of materials, making it easier for the nanofiber membrane to adsorb lithium-containing complexes in the solution, thereby making up for the loss of active lithium during the initial charge and discharge process, thereby improving the electrical performance of the battery.

[0049] Preferably, the solid phase treatment step in step A is: placing a porous lithium foil or lithium foil between the base membrane and the nanofiber membrane, and then performing hot pressing.

[0050] The base film usually refers to a thin film that serves as a carrier or support to facilitate the nanofiber membrane to adsorb lithium powder and later compensate for the loss of active lithium during the initial charge and discharge process.

[0051] Preferably, the nanofiber membrane prepared by electrospinning in step A has a diameter of 150-500 nm, a porosity of 50%-80%, and a thickness of 3 um-6 um.

[0052] A diameter in the range of 150-500nm means that these fibers have a larger specific surface area than conventional fibers, which makes the nanofiber membrane have better performance in applications such as filtration, catalysis, and adsorption. A porosity of 50%-80% means that the nanofiber membrane has good permeability and can accommodate and pass fluids or gases. At the same time, it has a large surface area and is suitable for gas filtration and liquid adsorption. A membrane thickness of 3-6μm is generally suitable for applications that require higher permeability, which facilitates better adsorption of lithium powder or lithium ions.

[0053] Preferably, in step C, the hot pressing pressure of the battery cell assembly is 5-10t, and the hot pressing temperature is 70-95°C.

[0054] The battery cells are mainly processed through hot pressing technology to ensure the stability of the internal structure of the battery and improve its performance. It is used to ensure that there is sufficient contact and bonding force between the various layers of materials in the battery cell, thereby avoiding gaps or uneven compaction inside the battery cell.

[0055] Example 2

[0056] The present invention provides a technical solution: a method for preparing a pre-lithiation battery cell, comprising the following steps:

[0057] S11. Place 10 g of polyacrylonitrile (PAN) powder in a vacuum drying oven and dry for 24 h.

[0058] S12, placing the dried polymer powder in 36 g of N,N-dimethylformamide (DMF) and heating to dissolve.

[0059] S13. The completely dissolved polymer solution was placed in a 60 mL syringe, and a flat nanofiber membrane was prepared by electrospinning process, wherein the high voltage was 10 kV, the flow rate of the spinning solution was 0.1 mL / min, the thickness of the nanofiber membrane was 5 um, and the diameter of the fiber membrane was 400 nm.

[0060] S2. Pre-lithiation treatment of flat nanofiber membrane

[0061] The prepared flat nanofiber membrane was immersed in a 10% concentration lithium-biphenyl / tetrahydrofuran solution at 45° C. for 12 h, and then dried in an oven at 45° C. for 12 h.

[0062] S3. Preparation of composite diaphragm

[0063] The PP base film and the pre-lithiation treated flat nanofiber membrane are hot pressed and composited between the rollers of a calender.

[0064] S4. Cell assembly

[0065] The composite diaphragm, the negative electrode, the composite diaphragm, the positive electrode, the composite diaphragm and the negative electrode are stacked into a unit, wherein the base film surface of the composite diaphragm is attached to the positive electrode, and the nanofiber film surface is attached to the negative electrode.

[0066] After the stacked battery cells are hot pressed, the battery cell assembly is completed.

[0067] Example 3

[0068] The difference between this embodiment and embodiment 2 is that the high voltage is 15 kV, the spinning solution flow rate is 0.4 mL / min, and the other preparation methods and conditions are the same as those in embodiment 2. The diameter of the prepared nanofiber membrane is 200 nm.

[0069] Example 4

[0070] The difference between this embodiment and embodiment 2 is that the polymer used is acrylic acid-maleic anhydride copolymer, and the other preparation methods and conditions are the same as those in embodiment 2.

[0071] Example 5

[0072] The difference between this embodiment and embodiment 2 is that the pre-lithiation treatment is to place a 5 um lithium sheet between the base film and the nanofiber membrane to form a sandwich structure, the composite temperature is 90°C, and the other preparation methods are the same as those in embodiment 2.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 2 is that the nanofiber membrane is not subjected to pre-lithiation treatment, and the other preparation methods are the same as those in Example 2.

[0075] Comparative Example 2

[0076] The difference between this comparative example and comparative example 2 is that all the separators of the lithium-ion battery are a 12 um base film plus a 3 um ceramic layer.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 2 is that the diaphragm adopts a 12um base film plus a 3um ceramic layer, and the pre-lithiation method is to short-circuit the negative electrode and the external lithium strip to perform pre-lithiation. The rest of the preparation method is the same as Example 2.

[0079] The discharge capacity and cycle retention rate of the embodiments and comparative examples are shown in Table 1 below. It can be found from the table that without pre-lithiation, the cycle effect of comparative example 1 is better than that of comparative example 2; after pre-lithiation, the finer the diameter of the nanofiber membrane, the better the pre-lithiation effect.

[0080] Table 1 Electrical properties of examples and comparative examples

[0081]

[0082] This application utilizes electrospinning to prepare a flat nanofiber membrane and performs a pre-lithiation treatment on it. The nanofiber membrane prepared by electrospinning has a larger specific surface area, and the hydroxyl and carboxyl groups on the chain have a higher adsorption capacity. On the other hand, the nanofiber membrane has a good liquid storage capacity and has a good effect on the migration of lithium ions during the charging and discharging process.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a pre-lithiation battery cell, characterized in that: Including the following steps: Step A: After the polymer powder is dried, it is placed in an organic solvent together with an additive, stirred and dissolved to form a spinning solution, a flat nanofiber membrane is prepared by an electrospinning method, and then the flat nanofiber membrane is subjected to liquid phase treatment or solid phase treatment to complete pre-lithiation; Step B: hot pressing the PP base film and the pre-lithiated flat nanofiber membrane through a calender roller to form a composite separator; Step C: stacking the composite separator, negative electrode, composite separator, positive electrode, composite separator, and negative electrode into a unit body, wherein the base film surface of the composite separator is attached to the positive electrode and the nanofiber membrane surface is attached to the negative electrode, and then assembling multiple units into a battery cell.

2. The method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: The polymer powder in step A is one or more of polyacrylonitrile, polymethyl methacrylate, acrylic acid-maleic anhydride copolymer, polytetrafluoroethylene, and polyvinylidene fluoride.

3. The method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: The weight average molecular weight of the polymer powder in step A is 30,000-250,000, and the drying time during the drying is 12-24 hours.

4. The method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: The organic solvent in step A is one or more of N,N-dimethylformamide, dimethyl sulfoxide and acetone.

5. The method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: During the dissolution in step A, the solution is heated and dissolved under the action of a multi-head magnetic stirrer, the dissolution time is 12-24 hours, and the dissolution temperature is 50-80°C.

6. A method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: In the spinning solution of step A, the mass fraction of polymer powder is 10-30 parts, the mass fraction of additives is 0-5 parts, and the mass fraction of organic solvent is 60-90 parts.

7. The method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: The liquid phase treatment step in step A is as follows: soaking the prepared flat nanofiber membrane in a 45°C lithium-biphenyl / tetrahydrofuran solution or a naphthalene-2-methyl-tetrahydrofuran lithium solution for 24-48 hours, with a solution concentration of 0.1M-1M, and then drying in an oven at 45°C for 12-24 hours.

8. The method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: The solid phase treatment step in step A is: placing a porous lithium foil or a lithium foil between the base film and the nanofiber membrane, and then performing hot pressing.

9. The method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: The nanofiber membrane prepared by electrospinning in step A has a diameter of 150-500 nm, a porosity of 50%-80%, and a thickness of 3 um-6 um.

10. The method for preparing a pre-lithiation battery cell according to claim 1, characterized in that: In the step C, the hot pressing pressure of the battery cell assembly is 5-10t, and the hot pressing temperature is 70-95°C.

Citation Information

Patent Citations

  • Isolating membrane and preparation method thereof, battery and electric device

    CN116914371A

  • Preparation method of pre-lithiated negative plate and lithium ion battery

    CN117457855A

  • Composite diaphragm and pre-lithiation method thereof

    CN117977112A

  • Composite diaphragm, preparation method thereof and lithium ion battery

    CN119009370A

  • Hollow fiber membrane as well as preparation method and application thereof

    CN119243417A